Energy Commons During Crisis: Understanding Housing Cooperative Strategies Through Dramaturgical Sociology - Jan Frankowski; Aleksandra Prusak; Jakub Sokołowski; Joanna Mazurkiewicz; Tomasz Świetlik (International Journal of the Commons)
The importance of energy as a common good becomes especially pronounced during crises. This paper reconstructs the response of housing cooperatives – a specific type of energy community – to the energy crisis. To this end, we apply eighteen impression management strategies inspired by Erving Goffman’s dramaturgical sociology. We analyse a unique dataset of annual reports from Polish rural housing cooperatives, which display a range of reactive, proactive, and collaborative attitudes to high energy prices and fuel shortages following the embargo on Russian coal in 2022. The energy crisis led four out of five rural housing cooperatives to adopt defensive impression management strategies. The three most common were crisis attribution (66%), resourceful management (18%), and deliberative silence (12%). These strategies appear to reflect an effort to position cooperatives within a dual role, balancing social and economic rationales. The collective attitudes undertaken by the cooperative boards to support common resources were also ambiguous, reinforcing existing power hierarchies and dominant logics rather than emerging from grassroots initiatives, due to the limited capacities and incentives in structurally disadvantaged areas. Therefore, our findings portray rural housing cooperatives as solitary and routine actors, undertaking an effort often beyond their capacities and call for their greater recognition as energy commons crucial for ensuring local energy security.